Correlations between and within generations and heritability of chips color, dry matter and yield in potatoes - Rodrigues, Andréa Felix Souza; Pereira, Arione da Silva (Pesquisa Agropecuaria Brasileira, 2003)
The objectives of this work were to determine correlations between and within clonal generation, to estimate heritability for chips color, dry matter content and yield of potatoes, and their implications on selection. Two hundred and fifty clones of ten families were randomly chosen from a first clonal population, directed to chips processing, of the potato breeding program of Embrapa-Centro de Pesquisa Agropecuária de Clima Temperado. The clones were evaluated in second (G2), third (G3) and fourth (G4) generations during autumn and spring of 1999 and autumn of 2000, respectively, in Pelotas, RS. The coefficients of correlation between generations and the estimates of heritability within clonal generations were low for chips color, low to moderate for dry matter and incremental with generations for yield components. The coefficients of correlations between quality and yield component traits within each generation were low and, the majority, non significant. The estimates of heritability of joint G3 and G4 data analysis were moderate, moderately high and high, respectively, for chip color, dry matter content and yield.